Drugs Involved in Dyslipidemia and Obesity Treatment: Focus on Adipose Tissue - Dias, S (2018)
Metabolic syndrome can be defined as a state of disturbed metabolic homeostasis characterized by visceral obesity, atherogenic dyslipidemia, arterial hypertension, and insulin resistance. The growing prevalence of metabolic syndrome will certainly contribute to the burden of cardiovascular disease. Obesity and dyslipidemia are main features of metabolic syndrome, and both can present with adipose tissue dysfunction, involved in the pathogenic mechanisms underlying this syndrome. We revised the effects, and underlying mechanisms, of the current approved drugs for dyslipidemia and obesity (fibrates, statins, niacin, resins, ezetimibe, and orlistat; sibutramine; and diethylpropion, phentermine/topiramate, bupropion and naltrexone, and liraglutide) on adipose tissue. Specifically, we explored how these drugs can modulate the complex pathways involved in metabolism, inflammation, atherogenesis, insulin sensitivity, and adipogenesis. The clinical outcomes of adipose tissue modulation by these drugs, as well as differences of major importance for clinical practice between drugs of the same class, were identified. Whether solutions to these issues will be found in further adjustments and combinations between drugs already in use or necessarily in new advances in pharmacology is not known. To better understand the effect of drugs used in dyslipidemia and obesity on adipose tissue not only is challenging for physicians but could also be the next step to tackle cardiovascular disease.